Necessary Disruptions: A Discussion of Daniel Butler's "Racialized Bodies and the Violence of the Setting". Issue 3 (3rd July 2019) - González, Francisco J.
ABSTRACT: This discussion of Daniel Butler's article "Racialized Bodies and the Violence of the Setting" takes up the importance of the concept of place, largely through the lens of Frantz Fanon. It argues that being is best understood as being placed, emphasizing the necessity of material and historical setting for any ontological formation. Very tentatively, it advances a fragile hope that Whiteness is currently being placed in a way that can no longer be regarded as something universalized and invisible.